2009
DOI: 10.1038/ng.356
|View full text |Cite
|
Sign up to set email alerts
|

BrafV600E cooperates with Pten loss to induce metastatic melanoma

Abstract: Mutational activation of BRAF is the earliest and most common genetic alteration in human melanoma. Hence, to build a model of human melanoma, we generated mice with conditional melanocyte-specific expression of BRafV600E. Upon induction of BRafV600E expression, mice developed benign melanocytic hyperplasias that failed to progress to melanoma over 15-20 months. By contrast, expression of BRafV600E combined with Pten tumor suppressor gene silencing elicited development of melanoma with 100% penetrance, short l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
1,252
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,051 publications
(1,326 citation statements)
references
References 50 publications
66
1,252
2
6
Order By: Relevance
“…2). This synergy was most powerfully corroborated in mouse transgenic models in which pairwise activation and inacti vation of NRAS and CDKN2A, BRAF and PTEN, or BRAF and CDKN2A, respectively, gave rise to melanoma with high fidelity 14,15 . Characterization of tumours from large cohorts of patients with advanced-stage melanoma at the whole-genome level has provided greater granularity regarding the overall prevalence of these genetic alterations, as well as their overlap 5,9,16 (FIG.…”
Section: Genetic and Immune Landscape Of Melanomamentioning
confidence: 84%
“…2). This synergy was most powerfully corroborated in mouse transgenic models in which pairwise activation and inacti vation of NRAS and CDKN2A, BRAF and PTEN, or BRAF and CDKN2A, respectively, gave rise to melanoma with high fidelity 14,15 . Characterization of tumours from large cohorts of patients with advanced-stage melanoma at the whole-genome level has provided greater granularity regarding the overall prevalence of these genetic alterations, as well as their overlap 5,9,16 (FIG.…”
Section: Genetic and Immune Landscape Of Melanomamentioning
confidence: 84%
“…In the first model, PKCi could be mediating downstream anti-senescent activity of the PI-3-kinase pathway, which prevents oncogene-induced senescence by a second oncogenic pathway. This model is suggested by data from mouse models of melanoma, where PI-3-kinase pathway signaling appears to prevent oncogene-induced senescence driven by mutant BRAF (Dankort et al, 2009). In an alternate model, PKCi might attenuate oncogene-induced senescence driven by the PI-3-kinase pathway itself.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured mouse embryonic fibroblasts, the PI-3-kinase inhibitors LY294002 and wortmannin induce senescence (Collado et al, 2000). In mouse models of melanoma, whereas BRAF activation in melanocytes mimics the generation of senescent cells described in human naevi, BRAF activation in mice deleted for PTEN leads to the formation of malignant tumors (Dankort et al, 2009). In contrast to these studies that indicate a role for the PI-3-kinase pathway in suppressing oncogene-induced senescence, other studies have indicated a role for the PI-3-kinase pathway in driving oncogene-induced senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Tyr-Cre-BRAF CA mice (B6.Cg- Braf tm1Mmcm Tg(Tyr-cre/ERT2)13Bos/BosJ) 27 were next crossed to the MC1R e/e , MC1R +/+ , MC1R R151C and MC1R C315S mice and BRAF V600E expression induced by tamoxifen administration. After UVB irradiation each week for four weeks (Extended Data Fig.…”
mentioning
confidence: 99%